The Improvement of Wear and Impact Resistance of High Chromium White Cast Iron for Crusher - Ridho Sabdo Prayogo; Lilik Dwi Setyana (Journal of Material Processing and Characterization, 2020)
Crusher is a component of heavy equipment used to break rocks or solid materials into a needed size. Crusher that is made of high chromium white cast iron will endure friction and impact forces. The quality improvement of the crusher is needed for enduring its service life. This research is conducted to determine the influence of heat treatment on the wear and impact resistance of the crusher. The material used in this research was high chromium white cast iron with some main compositions such as 18.5%wt Cr, 2.1%wt C, and 2.8%wt Ni. The heat treatment carried out was austenitization at a temperature of 1000ºC, followed by the quenching, quenching-tempering, normalizing, and annealing process. The tests carried out for the characterization of mechanical properties were Vickers hardness, impact, and wear rate. Meanwhile, observation was conducted to examine the microstructure of the specimen. Based on the observations, the microstructure of the specimen is dominated by M7C3 eutectic carbide, retained austenite and martensite. The highest hardness of the high chromium white cast iron (788 VHN) is a specimen with austenitizing-quenching (up 16% compared to normalizing specimens) and gradually decreases (up to 12%) after the 450ºC tempering. The highest wear resistance (8.1E-6 mm³/kg.m) is the specimen with tempering at 450ºC. The highest impact strength (0.055 J/mm²) occurs in the normalizing process. Hence, the heat treatment that can produce optimal properties to be applied in the crusher is tempering with the temperature of 450ºC.